Systematic Literature Review: Mathematics Learning for Children with Special Needs - Marhamah, Marhamah; Putri, Ratu Ilma Indra; Zulkardi, Zulkardi; Hartono, Yusuf (Indiktika : Jurnal Inovasi Pendidikan Matematika, 2025)
The aim of this research is to classify research related to mathematics learning in children with special needs into several categories. This Systematic Literature Review (SLR) research identifies, evaluates, and interprets research that is relevant to mathematics learning for children with special needs. Researchers reviewed 16 articles from 9 journal indexed by Scopus. The results of this research are in the form of classifying the content of the article into 5 categories, namely subjects, material, education level, methods, and student competencies, which can be used as recommendations in further research regarding mathematics learning for children with special needs. The classification results revealed that the most frequently studied research subjects were children with autism, accounting for 37.5% of the articles. In terms of instructional content, the most commonly explored topic was whole number operations, with a proportion of 42.86%. Regarding educational level, elementary school emerged as the most common focus, appearing in 56.25% of the studies. As for research methods, both qualitative and research and development approaches were used in 18.75% of the articles, respectively. Meanwhile, in terms of student competencies, conceptual understanding was the dominant focus, discussed in 41.67% of the reviewed studies.